Anxiety, Age, and Gender in Agitation Patients Installed Conventional Restraint in Inpatient Room - Heru Suwardianto; Sandy Kurniajati (Journal of Applied Nursing and Health, 2022)
Background: Some variables that may influence age and gender. The study aimed to determine whether there is a relationship between anxiety and gender in Agitation patients with conventional restraint in the Inpatient Room. Methods: This research method uses the correlation method with a cross-sectional design. A research sample is several patients who receive restrain intervention, totaling 27 respondents. The sampling technique was purposive, with the patient inclusion criteria on the RASS scale of +1 to -1. The family agreed for the patient to be a respondent. The independent variable is anxiety, while the dependent variable is age and gender. Anxiety instrument using FASS (Face Anxiety Scale Statistical Test using Spearmen rho with a <0.05. This study has received Ethical Approval from the STIKES Kediri Baptist Hospital. Results: The statistical test results on anxiety with age obtained a p-value of 0.051 with a <0.05, which means there is no relationship between anxiety and age in respondents with anxiety in patients with restraints. The results of statistical tests on the anxiety variable with sex get a p-value of 0.551 with a <0.05, which means that there is no relationship between anxiety and type gender in patients with restraint Conclusion: Age and gender have no relationship with anxiety in patients. Agitation is installed with Conventional Restraints in the Inpatient Room. For further research, it is necessary to use a more significant number of respondents to see the broader significance.